Financial evaluation of oil licensing contracts in Mayssan oil company for the period from 2012-2020 (case study) - Dr. Nada Ismaeel Jabouri Qammach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this study revolves around creating a framework for knowledge and application on the ground about how to evaluate the oil licensing rounds in (MOC) at the financial level as one of the important stages in the strategic strategy management stages. The main problem with the (MOC) remains that it does not have at least a real evaluation of the oil licensing contracts at the financial level, before and after the oil licensing contracts in the company. There must be a real evaluation of the licensing contracts in the (MOC) based on the foundations and integrated studies to judge the feasibility of these contracts in proportion to the nature of its work and the challenges it faces. Case study approach was adopted , and selected forms of financial criteria were used to assess the efficiency of the financial performance of its licensing rounds in line with the nature of its business. Based on all of the foregoing in this study, the results indicate that the appropriate evaluation for the current period is at least the financial evaluation of oil licensing contracts in the (MOC), given the importance of this criterion on performance and success. Organizations in light of the rapid and continuous developments and changes in the modern business environment.